A phase 1 study of combined guadecitabine and cisplatin in platinum refractory germ cell cancer. (1st November 2020) - Albany, Costantine; Fazal, Zeeshan; Singh, Ratnakar; Bikorimana, Emmanuel; Adra, Nabil; Hanna, Nasser H.; Einhorn, Lawrence H.; Perkins, Susan M.; Sandusky, George E.; Christensen, Brock C.; Keer, Harold; Fang, Fang; et al.
Abstract: Purpose: Germ cell tumors (GCTs) are cured with therapy based on cisplatin, although a clinically significant number of patients are refractory and die of progressive disease. Based on preclinical studies indicating that refractory testicular GCTs are hypersensitive to hypomethylating agents (HMAs), we conducted a phase I trial combining the next‐generation HMA guadecitabine (SGI‐110) with cisplatin in recurrent, cisplatin‐resistant GCT patients. Methods: Patients with metastatic GCTs were treated for five consecutive days with guadecitabine followed by cisplatin on day 8, for a 28‐day cycle for up to six cycles. The primary endpoint was safety and toxicity including dose‐limiting toxicity (DLT) and maximum tolerated dose (MTD). Results: The number of patients enrolled was 14. The majority of patients were heavily pretreated. MTD was determined to be 30 mg/m 2 guadecitabine followed by 100 mg/m 2 cisplatin. The major DLTs were neutropenia and thrombocytopenia. Three patients had partial responses by RECIST criteria, two of these patients, including one with primary mediastinal disease, completed the study and qualified as complete responses by serum tumor marker criteria with sustained remissions of 5 and 13 months and survival of 16 and 26 months, respectively. The overall response rate was 23%. Three patients also had stable disease indicating a clinical benefit rate of 46%. Conclusions: The combination of guadecitabine and cisplatin was tolerable and demonstrated activity in patients with platinum refractory germ cell cancer. Abstract : A phase I trial demonstrates tolerable toxicity and clinical activity for combining the hypomethylating agent guadecitabine with cisplatin for testicular cancer patients that have failed prior chemotherapy. This strategy has the potential to be the first targeted treatment for chemotherapy refractory testicular cancer.